Ayurvedic Management of Metabolic Disorder w.r.t. Prameha, Medorog (AYUSHDHARA, 2025)
Metabolic disorder is characterized by chronic hyperglycemia with disturbances of carbohydrate, fat and protein metabolism resulting from defects in insulin secretion, insulin action. The disease in which there is increased in quantity and frequency of urination in Ayurved is called Prameha. Prameha as the word says, “Prakarsena Prabhutam Pracuram Varam Varam Va Mehati Mutratvagam Karoti Iti prameha.” Dyslipidemia refers to an abnormal level of lipids (fat) in blood, including cholesterol and trigycerides. It is symptomatically similar to the Medoroga in Ayurveda. Medhodushti is explained as vitiation in Prakrit karya of Medho Dhatu. It might be like Medoroga in Ayurveda. Excess of Meda Dhatu is referred to as Medo Roga and deranged Angi is the root cause of this disease. According to the WHO, 39% of the world adult population has been affected by elevated blood cholesterol, with a relatively higher prevalence among women (40%) than among men (37%). Raised blood cholesterol can have many consequences that include central obesity, insulin resistance, hypertension, dyslipidemia, high triglycerides, and low HDL. A 50yr old male came to Ch. Brahm Prakash Ayurved Charak Sansthan in special OPD of Kayachikitsa with Breathlessness on excertion, pain in calf muscle, fatigue and tiredness etc. Complete history taking with examination and investigation conclude to diagnosis of metabolic disorder (Pramrha, Medoroga), so patient was treated with internal Ayurvedic herbal formulation, Pathya, Apathya including complete diet chart and Yogasanas. The treatment modalities done showed marked improvement in the patient’s signs and symptoms and blood investigations and hence, treatment through Ayurveda has effective results in the management.